Economic analysis of indigenous small ruminant breeds in the pastoral system: A case of sheep and goats in Marsabit district, Kenya - Omondi, Immaculate A. (Egerton University, 2008)
Small ruminants provide very important genetic resources that can be exploited for continued improvements of the livelihoods of poor livestock keepers in the pastoral production system, particularly in the developing country situation, Kenya being one of them. Though important, the motivation of livestock keepers to hold and maintain particular AnGr in conditions of decreasing animal genetic resource base is imperfectly understood. Consequently, in an endeavour to improve the livelihoods of resource-poor small ruminant livestock keepers, it is important to understand the underlying drive that motivates livestock keepers to keep and maintain particular AnGR. This can be achieved if producer responses in production that lead to either loss or conservation of these resources are sufficiently known. This study contributes to the existing knowledge gap by analysing the status of small ruminant breeds in the pastoral production system in Marsabit district of Kenya. Primary data, collected from livestock keepers using structured questionnaires, revealed that small ruminants contribute enormously towards livestock keepers’ livelihoods, especially the poor, and subsequently, to conservation of the resource. The results obtained from multinomial logit models derived from stated choice data collected from 314 respondents in the semi-arid Marsabit district of Kenya reveal that disease resistance is the most highly valued trait whose resultant augmentation results into a welfare improvement of up to KShs.3082 and 1480 in goats and sheep, respectively. In goats, drought tolerance and milk traits were found to be implicitly valued for up to KShs.2695 and 1163 respectively, while in sheep, drought tolerance and fat deposition traits were found to be implicitly valued at KShs.973 and 748 respectively. The study further revealed that improvement in milk trait in does, body size and disease resistance traits in bucks, and drought tolerance trait in both does and bucks will collectively improve the producers’ welfare hence should be given priority. However, improvement in the reproduction and production (“overall body condition/ meatiness” trait) potential of goats will be worthwhile only if issues concerning access to pasture and water resources are addressed prior and simultaneously. The results further point out that for livestock stakeholders to effectively improve the livelihoods of poor livestock-keepers, development strategies for improving the management and/ or utilisation of small ruminant genetic resources in terms of drought tolerance in sheep, should not only be tailor made to target regions that are frequently devastated by drought but should also precede other strategies or efforts that would first lead to the improvement of producers’ economic status.